Reconstructing the gendered subaltern subject: Chinese rural migrant women in literary translation. - Dong, Yijia (Perspectives: Studies in Translatology, 2024)
As a significant embodiment of Chinese subalternity, the subject formation of rural migrant women presents the multiple power dynamics emerging in the course of modernisation, industrialisation and urbanisation in post-reform China. Northern Girls, a novel written by contemporary Chinese female writer Sheng Keyi, provides a realistic account of survival for this marginalised group of women that is intertwined with class, gender and rural–urban disparities. This paper takes this novel as a case study, exploring how the female subaltern subject is discursively reconstructed through literary translation. Regarding the English translation as part of the transcultural flow of ideas between Western and indigenous Chinese feminisms, this paper examines its translation strategies, demonstrating how gender stereotypes, misogynous discourse, power relations and female agency in a gendered subaltern narration are rewritten in a hegemonic language. The analysis reveals that the English version rearranges the intersectional dynamics of power in post-reform China. While the gendered autonomy and agency are reinforced in the target text, the discursive construction of the Chinese female subaltern is simplified by a hegemonic formation of feminism and modernity that underplays the original 'reverse discourse' in non-Western women's writing.